Conan the barbarian (1981) [videorecording (DVD)] - Milius, John; Schwarzenegger, Arnold; Jones, James Earl; Bergman, Sandahl; Howard, Robert E. (Robert Ervin), 1906-1936 (Universal Studios Home Video, 2000)
Cimmerian Conan is captured as a child after his parents are murdered by raiding Vanir led by Thulsa Doom. After years of enslavement, Conan is freed to learn the "riddle of steel" and to kill the arch-villain Thulsa Doom.